2017
DOI: 10.1021/acs.joc.7b00065
|View full text |Cite
|
Sign up to set email alerts
|

Mild Method for 2-Naphthylmethyl Ether Protecting Group Removal Using a Combination of 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) and β-Pinene

Abstract: The use of a combination of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) and β-pinene permits the removal of 2-naphthylmethyl (Nap) ether protecting groups on highly sensitive substrates. The reaction tolerates both acid and base sensitive protecting groups, and products are afforded in 68–96% yield. The utility of the method is demonstrated by the removal of the Nap protecting groups on highly sensitive 2,6-dideoxy-sugar disaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 29 publications
(111 reference statements)
0
48
0
Order By: Relevance
“…The Nap protecting group has emerged as a particularly valuable addition to carbohydrate chemistry [ 24 25 ]. Not only does it not significantly alter carbohydrate reactivity, it also can be readily cleaved under hydrogenolytic conditions as well as a variety of oxidative [ 26 ] and acid-mediated conditions [ 25 , 27 ] that are orthogonal to benzyl ethers.…”
Section: Discussionmentioning
confidence: 99%
“…The Nap protecting group has emerged as a particularly valuable addition to carbohydrate chemistry [ 24 25 ]. Not only does it not significantly alter carbohydrate reactivity, it also can be readily cleaved under hydrogenolytic conditions as well as a variety of oxidative [ 26 ] and acid-mediated conditions [ 25 , 27 ] that are orthogonal to benzyl ethers.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, a variety of new reagent combinations were introduced which increase the utility of Nap Protecting group. For example, Bennett employed β‐pinene as acid scavenger, Crich used hydrogenation using Pd/C poisoned with thioether, Codée discovered HCl and HFIP, and Liu introduced HF‐pyridine as novel reagents. Borbas and co‐workers recently showed that catalytic hydrogenation can be effectively used for selective deprotection of the (2‐naphthyl)methyl (NAP) group in the presence of p ‐methoxybenzyl (PMB), benzyl and benzylidene groups in a series of monosaccharides .…”
Section: New Reagents For Old Protecting Groupsmentioning
confidence: 99%
“…48 Confronted with such problems in our laboratory we were intrigued by the possibility of employing 2-naphthylmethyl (Nap) ethers in place of benzyl ethers. 2-Naphthylmethyl ethers have enjoyed widespread use and continuous refinement in carbohydrate chemistry as surrogates for p -methoxybenzyl ethers since their introduction to the field by Matta, 914 because of their greater stability to Brønsted acids but comparable ease of removal under oxidative conditions with dichlorodicyanoquinone. However, it was the selective hydrogenolytic removal of Nap ethers in presence of benzyl ethers initially reported by Spencer 15 that suggested the possibility of their use as a possible remedy to the problem in hand.…”
Section: Introductionmentioning
confidence: 99%